Higher plant myosin XI moves processively on actin with 35 nm steps at high velocity - Tominaga, Motoki (Oxford University Press, 2003)
High velocity cytoplasmic streaming is found in various plant cells from algae to angiosperms. We characterized mechanical and enzymatic properties of a higher plant myosin purified from tobacco bright yellow-2 cells, responsible for cytoplasmic streaming, having a 175 kDa heavy chain and calmodulin light chains. Sequence analysis shows it to be a class XI myosin and a dimer with six IQ motifs in the light chain-binding domains of each heavy chain. Electron microscopy confirmed these predictions. We measured its ATPase characteristics, in vitro motility and, using optical trap nanometry, forces and movement developed by individual myosin XI molecules. Single myosin XI molecules move processively along actin with 35 nm steps at 7 μm/s, the fastest known processive motion. Processivity was confirmed by actin landing rate assays. Mean maximal force was ∼0.5 pN, smaller than for myosin IIs. Dwell time analysis of beads carrying single myosin XI molecules fitted the ATPase kinetics, with ADP release being rate limiting. These results indicate that myosin XI is highly specialized for generation of fast processive movement with concomitantly low forces.